CHALLENGES OF INDONESIAN TEACHER COMPETENCE IN DEALING WITH ASEAN ECONOMIC COMMUNITY (AEC) - Meita Lesmiyati Khasyar (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2021)
This article examines the professional competence of teachers in the face of the MEA. The method in this paper describes a problem that there is in the competence of teachers in Indonesia in the face of the MEA. MEA is a form of realization of the ultimate goal of economic integration in Southeast Asia. In 2015 an agreement ASEAN Economic Community (AEC) or the ASEAN Economic Market comes into force. This agreement not only have an impact on the economic sector, but also in other sectors. No exception